HUBUNGAN TINGKAT PENDIDIKAN DAN TIPE POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK USIA PRASEKOLAH - ALINI ALINI; INDRAWATI INDRAWATI (Jurnal Ners, 2020)
Parenting patterns of people in guiding children to achieve their psychosocial development tasks properly, cannot be separated from the level of parental education which supports parents' knowledge of understanding good parenting styles in achieving psychosocial development in preschool children. This study aims to determine the relationship between the level of education and the type of parenting style with the psychosocial development of preschool children in TK Pertiwi Bangkinang. This research is a quantitative analytic study with a cross sectional research design. The affordable population in this study were all parents of all preschool children who attended Kindergarten Pertiwi Bangkinang, totaling 100 people. The sampling technique was done by means of consecutive sampling. Data analysis using the chi suare test. The results showed that there was a significant relationship between the level of parental education and the type of parenting towards psychosocial development in early childhood (preschool) at TK Pertiwi Bangkinang Kota (P value = 0.000 (p value â‰¤ Î± 0.05). Parents are expected to be sensitive to their needs. One way of doing this is by using appropriate parenting styles, while appropriate parenting is democratic parenting.